PERBANDINGAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA YANG MENGIKUTI TPA DAN TIDAK MENGIKUTI TPA DI MI PLUS DARUL ILMI BANJARBARU - Fitriani Fitriani; Imaniah Elfa Rachmah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
This study discusses the comparison of the ability to read Al-Qur'an of students who take TPA and not follow TPA at MI Plus Darul Ilmi Banjarbaru. The purpose of this research is to find out how much the comparative reading ability of the Koran of students who take the TPA and not take the TPA in MI Plus Darul Ilmi Banjarbaru and whether there is a difference. This study uses a quantitative approach, the population in this study were all fifth-grade students at MI Plus Darul Ilmi. As for what has been determined as a sample in this study, 40 respondents were consisting of, 20 students who were TPA and 20 students who were not TPA. Data mining, the writer uses observation, tests, and documentation techniques. Descriptive data analysis techniques and hypothesis testing using the t-test formula. Based on the results of research to test the hypothesis about the differences in learning outcomes of the two groups above, the results obtained "t" test of 3.71. These results the author gives an interpretation of the table with a degree of freedom (dB) of 40 so that it is obtained: at a significance level of 5% or 1%. It turns out that the price of the "t" test obtained is far greater than the t table both at a significance level of 5% and 1% which is 2.71 2.02. So it can be concluded that the alternative hypothesis (Ha) which states there is a significant difference between the comparison of the ability to read Al-Qur'an TPA and No TPA in MI Plus Darul Ilmi Banjarbaru. Keywords: Comparison, Ability to read Al-Qur'an, Madrasah Students.